Antenatal diagnosis of myometrial invasion in anterior placenta previa by transabdominal color Doppler ultra sound - Sulaiman, Jwan N. (AL-Kindy College Medical Journal, 2011)
Background: The incidence of maternal mortality inplacenta previa accrete is 7%,and its preoperativediagnosis is of a great value.Objective: to evaluate the efficacy of transabdominalcolor Doppler ultrasound in diagnosing placentaprevia accreta and inccreta. Color Doppler imagingcriteria used in: includes diffuse parenchymalplacental lacunar flow, focal intra parenchymalplacental lacunar flow and bladder uterine serosainterphase hyper-vascularity.Design: Prospective study on patients fromJanuary2007 to January 2008.Patients and method: 48patients with one caesareansection or more and with persistent anterior placentaprevia diagnosed by transabdominal ultrasound wereexamined by color Doppler at 32 or more weeks ofgestation to determine the possibility of myometrialinvasion depending on the above color Dopplercriteria.Results: Out of 48 patients eleven exhibitedcharacteristic Doppler imaging pattern highly specificfor placenta accreta and inccreta according topreceding criteria , one patient had false positive colorDoppler imaging result, 5 patients underwentcaesarian hysterectomy , the remaining five weretreated conservatively by uterine artery ligation andother conservative measures because of bleedingfrom the lower uterine segment.Conclusion Color Doppler sonography is highlysensitive andspecific in the antenatal diagnosis of placenta previaaccreta .If a strong suspicion is found before delivery,appropriate location and timing for delivery should beconsidered ,to allow access to adequate surgicalpersonel and equipment ,preoperative bloodpreparation to reduce morbidity and mortality.Journal titleUltrasound in obstetric and gynecology ISSUN 0960-7692 Source 2000 Vol 15 In 1 PP. 28-35 (22rel)